A bittersweet day - Singh, Aftar (2014)
National shooter Mohd Ezuan Khan broke the national record en route to the gold medal but it was Mohd Hassanul Adzhar Mohd Badrin who hogged the timelight in the man's 50m rifle prone event in the Selangor Open Shooting Championships at the Subang Shooting Range.